ChemInform Abstract: Indium versus Gold Catalysis in Dehydrative Reactions with Allylic Alcohols. Issue 16 (March 2016) - Webster, Stacey; Schaefer, Louise; Barker, Graeme; Lee, Ai‐Lan
Abstract: Indium(III) chloride is a more efficient catalyst than gold catalysts in dehydrative reactions of allylic alcohols with alcohols, thioacid, and thiophenols.